Case of vascular air embolism during holmium laser enucleation of the prostate. (13th November 2014) - Kato, Takuma; Sugimoto, Mikio; Matsuoka, Yuki; Sakura, Yuma; Hayashida, Yushi; Hirama, Hiromi; Tsunemori, Hiroyuki; Ueda, Nobufumi; Uemura, Naoya; Miyawaki, Yuki; Shirakami, Gotaro; Kakehi, Yoshiyuki
Abstract Vascular air embolism is a rare complication during transurethral surgery. A case of air embolism during holmium laser enucleation of the prostate in a 76‐year‐old man is presented. During the step of morcellation, the patient's blood pressure suddenly oscillated up and down, and end‐tidal CO2 and arterial saturation decreased. Transesophageal and transthoracic echocardiography showed air collection in the right atrium. It was also discovered that incorrect assembly of the tube from the morcellator caused rapid entrainment of air into the vein. Computed tomography and abdominal X‐ray showed niveau formation in the femoral vein and air collection in the pelvic retroperitoneal space. The patient recovered with careful observation and was discharged 7 days after the operation with no sequelae. This report is presented to remind urologists of this unusual complication that can occur during holmium laser enucleation of the prostate procedures.